THE EFFECTS OF STORAGE TEMPERATURE AND TYPES OF MEDIA ON THE SURVIVAL RATE OF S. agalactiae BACTERIOPHAGE - Angela Mariana Lusiastuti; Tuti Sumiati; Adin Priadi (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2008)
The successful effect of phages in phage therapy has been proven by an increase of the presence of phages in survivors. Seven previously isolated phages were used to examine the effects of storage temperature and types of media on their survival rate. Phages PSaT-18, PSaT-19, PSaT-20 and PSaT-21 isolated from a Streptococcosis-infected Tilapia (Oreochromis niloticus) were used in this study. Phages PSaG-1, PSaG-2 and PSaG-3 were isolated from a diseased Gouramy (Osphronemus gouramy). All of the phages were stored in refrigerator at temperature of 8oC and kept in two types of media, Brain Heart Infusion Broth (BHIB) and BHIB enriched with glycerol. To determine the lytic activity of the phages, 20 μL of each phage suspension was poured onto BHIA plate and incubated at 25oC for 24 to 48 hours. The result showed that phages PSaT-18, PSaT-19, PSaT-20 and PSaT-21 have lytic activity against S. agalactiae and S. iniae than phages PSaG-1, PSaG-2, and PSaG-3. Phages PSaT-18, PSaT-19, PSaT-20, and PSaT-21 always survived up to three weeks and phage PSaT-18 in BHIB have the highest potential as a candidate of phage therapy for Streptococcosis.